Infection in multiple myeloma - Nucci,Marcio L. M. (2009)
Infections are significant causes of morbidity and the leading cause of death in patients with MM. Therapeutic strategies impact differently on the immune system, predisposing patients to various opportunistic infections. Myeloma and treatment-associated organ dysfunctions and co-morbidities also increase the risk of infection. Prospective epidemiologic studies of infections of myeloma patients from six centers from Brazil and one from Chile were performed. A total of 228 infectious episodes (median of 1; range: 1-13) were observed in 156 patients during one year. Median age was 57 years (range: 33-89), and 112 were men. Seventy-one percent of episodes occurred in Stage III (Durie-Salmon). Patients were divided into three phases according to the time of occurrence of infection related to the treatment of myeloma: phase 1 = induction therapy, phase 2 = during HCT and phase 3 = maintenance therapy or in relapse. Active myeloma and renal failure were risk factors in Phase 1; respiratory tract infections (46%) and urinary tract infections (21%) were the most frequent. In Phase 2, the risk factors were central venous catheters, neutropenia and mucositis; bacteremia (31%) and fever of unknown origin (23%) were the most frequent characteristics. Patients who were receiving corticosteroids were more probable to suffer infections in Phase 3 the most common being respiratory tract infections (44%). Rates of infectious-related death were 14.5% in phase 1, 5% in phase 2 and 14% in phase 3 (P=NS). The introduction of novel life-prolonging therapies has transformed myeloma into a chronic disease. Resulting cumulative immunosuppression has increased the risk of infection and expanded the spectrum of potential pathogens in this patient population. Infections continue to represent a major challenge for clinicians caring for myeloma patients.